Lifelong learning for inmates - Rozeman Abu Hassan (2014)
Lifelong learning could not only be learnt by the public but also by inmates in prisons. Open University Malaysia (OUM) had given the opportunity to inmates in Sekolah Integriti Kajang (SIK), Kajang Prison to obtain higher education in their fields of interest. As a university, OUM emphasized on the concept of Service to Society – not only to the public but also to inmates in prison. All this while, a stigma exists; the inmates have no place in the society and their future is assumed to be bleak. Nevertheless, the perception is changed after collaboration between OUM and the Prison Department of Malaysia. This had given the inmates a learning opportunity in pursuing their studies from the first degree to the master’s degree. Being a university that focused on online learning, OUM had provided a flexible learning system to the inmates. Hence, they were able to follow the courses in the programs offered to them. The role played by OUM in offering the education programs mark significant efforts in changing the path for inmates to lead productive lives in society. This had enabled a change in the society’s perception towards the inmates in leading a better future after life in prison. The impact of education is especially evident in prison. Rigorous study gives prisoners the intellectual leverage they need to revise their views of themselves and leave prison better equipped to contribute positively to their families and communities. Studies have shown that those released prisoners who received an education had a significantly lower rate of recidivism. (Abstract by author)